Deformation state of short-period AlGaN/GaN superlattices at different well-barrier thickness ratios - Kladko, V.P.; Safriuk, N.V.; Stanchu, H.V.; Kuchuk, A.V.; Melnyk, V.P.; Oberemok, A.S.; Kriviy, S.B.; Maksymenko, Z.V.; Belyaev, A.E.; Yavich, B.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Dependence of deformation characteristics changing in superlattice (SL)
structures AlxGa₁₋xN/GaN with Al (~10%) on the well-barrier thickness ratio in period
was studied in this work. The deformation state of SL and individual layers, relaxation
level and periods, layers’ thickness and composition of AlxGa₁₋xN layers were analyzed
using high-resolution X-ray diffractometry. It was ascertained that the buffer layer and
SL layers are compressed in all the investigated structures. Thus, it has been shown that
deformation of the SL period depends on the well/barrier thickness ratio. Thicknesses of
individual layers in SL strongly depend on the deformation state of the whole system.
Increasing the deformation level leads to the increase of the barrier layer thickness.